The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5007/1982-5153.2019v34n73p464
|View full text |Cite
|
Sign up to set email alerts
|

Desenho organizacional da rede de agentes que envolvem as parcerias público-privadas de saúde na Região Metropolitana de Salvador

Abstract: Este trabalho analisou as parcerias público-privadas (PPPs) stricto sensu de saúde existentes na Região Metropolitana de Salvador (RMS) (Hospital do Subúrbio, Instituto Couto Maia e Diagnóstico por Imagem) e identificou os agentes públicos e privados que envolvem essas concessões. Além disso, construiu um mapa de rede com o objetivo de delinear um desenho organizacional que compreende esses agentes, bem como investigou a quem se destinam as maiores responsabilidades desse sistema: se para o Estado ou para empr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The conclusion reached herein agrees with that of Silva, Carvalho and Oliveira (2019), that is, the greatest responsibilities are directed to the public sector. We found that the government of Bahia is largely responsible for preparing projects, and is also the incentive and fundamental agent in this process, since it allows and legitimizes the strategies of private agents, regulates, supervises and creates funding channels, which are mostly carried out by public agencies, and pays the bills through monthly pecuniary payments and resource and remuneration fees.…”
Section: Analysis Of Urban Mobility and Health Ppps In Bahiasupporting
confidence: 88%
See 3 more Smart Citations
“…The conclusion reached herein agrees with that of Silva, Carvalho and Oliveira (2019), that is, the greatest responsibilities are directed to the public sector. We found that the government of Bahia is largely responsible for preparing projects, and is also the incentive and fundamental agent in this process, since it allows and legitimizes the strategies of private agents, regulates, supervises and creates funding channels, which are mostly carried out by public agencies, and pays the bills through monthly pecuniary payments and resource and remuneration fees.…”
Section: Analysis Of Urban Mobility and Health Ppps In Bahiasupporting
confidence: 88%
“…Regarding methodology, this study followed an exploratory-descriptive qualitative approach and used comparative and monographic procedures. Therefore, the following steps based on methods adopted by Silva, Carvalho and Oliveira (2019), were used and are synthesized in Figure 1: 1) National and international bibliographic survey: books, book chapters, dissertations, theses, well-qualified articles and events. 2) Document review of norms and laws from Brazil, specifically Bahia, about PPPs, on official state and federal government websites.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations